2006
DOI: 10.1051/vetres:2005046
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Mycoplasma synoviae in hens after two enrofloxacin treatments and detection of mutations in the parC gene

Abstract: -The ability of Mycoplasma synoviae, an avian pathogen, to persist despite fluoroquinolone treatments was investigated in hens. Groups of Mycoplasma-free hens were experimentally infected with the M. synoviae 317 strain and treated twice with enrofloxacin at the therapeutic dose. The results show that the two treatments did not have any influence on this strain of M. synoviae recovery from tracheal swabs. Mycoplasmas were isolated from tracheal swab cultures, but not from inner organs such as the liver or sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
(47 reference statements)
1
31
0
1
Order By: Relevance
“…Descriptions of mechanisms involved in quinolone resistance in veterinary medicine are scarce Le Carrou et al, 2006). Reinhardt et al (2002) showed the presence of alterations on the four target genes encoding DNA gyrase and topoisomerase IV in M. gallisepticum enrofloxacin mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptions of mechanisms involved in quinolone resistance in veterinary medicine are scarce Le Carrou et al, 2006). Reinhardt et al (2002) showed the presence of alterations on the four target genes encoding DNA gyrase and topoisomerase IV in M. gallisepticum enrofloxacin mutants.…”
Section: Resultsmentioning
confidence: 99%
“…None of the susceptible strains had a change at these positions. A previous study reported that position 81 of the ParC QRDR may be implicated in En resistance in M. synoviae (6). Positions 80 and 84 of the ParC QRDR are known hot spots for En resistance in many bacteria, including mycoplasmas, and may alone or together with a mutation within the GyrA QRDR result in decreased susceptibility to fluoroquinolones (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone resistance occurs primarily through mutations in the quinolone resistance-determining regions (QRDRs) of the parC and/or gyrA gene (encoding the A subunits of DNA gyrase and topoisomerase IV) or the gyrB and/or parE gene (encoding the B subunits of DNA gyrase and topoisomerase IV). Topoisomerase IV (parC gene) has been suggested to be the primary target of En in M. synoviae, based on in vivo selection of strains with decreased susceptibility after experimental infection (6).…”
mentioning
confidence: 99%
“…Thus, it is more probable that M. suis developed tetracycline resistance mechanisms. In a study of M. synoviae, an increase in resistance to enrofloxacin could be demonstrated after several in vivo treatments of experimentally infected hens (27). However, when we used a microarray-based detection assay used to screen for antibiotic resistance genes in gram-positive The presence of M. suis within porcine erythrocytes nonetheless has significant clinical implications.…”
Section: Discussionmentioning
confidence: 99%